The Market Economy as a Social System - Tsukada, Hiroto (Springer Singapore, 2018)
This book develops John Rawls's theory of justice by adding reality-based analyses. This is accomplished by answering the question of who makes rules and how, and by providing new answers to three of today's most practical and critical issues. The question of who and how makes rules is discussed first; and group orientation instead of individualism, and a balance of negotiating power instead of a veil of ignorance are presented as new answers to this question. Based on this new understanding of rulemaking, three important practical rules are subsequently discussed: the rule of distribution of land and other natural resources, including the question of natural talent or who should bear the costs of children's education; the rule of distribution of products; and what motives support our acts of kindness. These rules are all dealt with from a shared perspective, viewing society as a single integrated construct. Equal distribution of land, not private but public payment of education fees, strengthening employees' bargaining power, and moving toward nobility-based kindness are put forward as central answers. By addressing critical questions on social rules and proposing answers, this book provides reliable principles to fall back on in our daily lives, and in our rapidly changing, globalized world. .